Teaching Pronunciation Skills (Texas Journal of Multidisciplinary Studies, 2022)
This article focuses on making teachers think about teaching English pronunciation, getting acquainted with the techniques of teaching pronunciation, exploring your own experience of using the techniques. The aim of the article is consideration the significance of developing learners’ pronunciation skills in teaching English.